Firm investment behavior in Kenya - Ng’ang’a, Jacob C (Journal of Entrepreneurship, Business and Economics, 2015)
To promote growth manufacturing industry in Kenya, the government must address various chal-lenges that include low level of investment. But this first require that the policy makers to have under-standing of firm‟s investment behavior to inform possible policy interventions. This paper uses modest panel data analysis to explain how interest rate, firm size, cash flow, uncertainty and locality of a firm impact on firm‟s investment in Kenya. The study finds that the cash flow has a significant influence on investment and relatively smaller firms invest proporionally more than larger firms. The study thus recommends policy shift towards stimulating investment in small firms, relative to large firms and rolling out financing models to build capacity in emerging firms. Research paper Reference to this paper should be made as follows: Ng‟ang‟a, P. (2015). “Firm investment behavior in Kenya”, Journal of Entrepreneurship, Business and Economics, Vol. 3, No. 1, pp. 81–104.